Physical Activity and BMI among Higher Secondary Students of Government Schools in Siliguri Sub-division of Darjeeling District, West Bengal - Kallol Bhandari; Tushar Kanti Saha; Abhijit Mukherjee; Sharmistha Bhattacherjee (Bengal Physician Journal)
Background: In India, the problems of underweight and overweight/obesity runs hand in hand. As the age increases from childhood to adolescent, the burden of overweight/obesity is found to be increased than underweight. Objectives: To evaluate the level of physical activity (PA) among school-going adolescents and explore its association with body mass index (BMI). Methods: Descriptive study with cross-sectional design was conducted in Government Higher Secondary Schools in Siliguri sub-division, Darjeeling district, from May 2019 to September 2020. Multistage random sampling was done. Sample size was 1,012. International Physical Activity Questionnaire (IPAQ) self-administered questionnaire was used. Collected data were entered into Microsoft Excel and analyzed by SPSS (version 22). Results: Mean BMI was 21.02 (SD ± 3.59) kg/m2. The majority (71.2%) had normal BMI, 19.4% were overweight, and 9.4% were underweight. Most (54.45%) do moderate PA, and 34.98% do high PA. The proportion of overweight people was highest among those with low PA (89.7%) and lowest among those with high PA (4%). This association was statistically significant (p < 0.001). The low PA category as compared to moderate PA had significantly higher odds of being overweight than normal BMI. But the high PA as compared to moderate PA had significantly lesser odds of being overweight than normal BMI. Conclusions: The prevalence of both overweight and underweight was higher among rural participants. Physical activity level was moderately negatively correlated with BMI. Study findings would be helpful to take proper planning and actions to prevent such problems.